PENGARUH PERPUTARAN KAS PERPUTARAN PERSEDIAAN TERHADAP PROFITABILITAS PADA PD. MOCHI LAMPION KASWARI KOTA SUKABUMI - Lesmana, Ardi (Jurnal Ilmu Manajemen Retail Universitas Muhammadiyah Sukabumi, 2020)
In a competitive business enterprise at present, the company's progress more rapidly. Competition is a problem that arises from outside the company where the competition will arise from other similar companies. In improving the profitability of the company, PD. Mochi Lampion Kaswari invest their working capital into cash turnover and inventory turnover for the purposes of company that you want to accomplish. The variables of this study consisted of cash turnover, inventory turnover and profitability as an independent variable as the dependent variable. With a ratio measurement scale. The population of this study are the financial statements of PD. Mochi Lampion Kaswari, while the sample used is the monthly financial statements of the company in 2011-2013. The type of data used is primary data, the data is sourced from the company. The data that has been collected analyzed using SPSS 17. And analyzed by using methods of classical assumption test, prior to testing the hypothesis that consists of a t-test, f and test the coefficient of determination. To prove the hypothesis used multiple linear regression. The results showed that the cash turnover, inventory turnover effect on profitability. At t test and f test known effect of independent variables on the dependent variable. Where the inventory turnover is more influential than the cash turnover on profitability.